Cousin [compact disc] (Sony Music, 2023)
Wilco's thirteenth studio album was recorded in the band's legendary Chicago studio, The Loft, over a period of two years. The ten new tracks are written by band leader Jeff Tweedy and feature musical performances by the longtime lineup of Nels Cline, Mikael Jorgensen, Glenn Kotche, John Stirratt, Pat Sansone and, of course, Tweedy on lead vocals. After a short detour back into their country-influenced roots via last year's Cruel Country double album, this release sees Wilco back in their more familiar progressive and experimental rock territory. Tweedy's singular songwriting voice is in full evidence, with lyrics weaving across a variety of topics, from the iconoclastic to the introspective.